Effects of maternal age, parity and hemoglobin on neonatal stature and cord blood hemoglobin: an observational study - Tiwari, Namrata; Mishra, Vinay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: There is a large body of research both in India and abroad studying the effect of maternal age, parity and haemoglobin (in third trimester) on their infant’s birth weight. The present study has been planned to evaluate these factors effects on their infant’s stature(anthropometry) and cord blood haemoglobin. Methods: Maternal background information, third trimester haemoglobin concentration, gestational age and number of children was obtained and recorded in semi-structured case proforma. 100 post-partum women and their newborns were studied in post-natal ward of a tertiary care hospital in an urban area. Maternal and neonatal data and anthropometric measurements were recorded in semi-structured case proforma. Results: Of the 100 newborns, 43% were second born, followed by 35% first born, 18% third born and only 4% were fourth born by the order of their birth. Out of the 100 studied mothers 52% were anaemic as per the WHO criteria (Hb <11 gm%). Cord blood haemoglobin values decreased significantly as the order of birth increased. The cord blood haemoglobin of normal birth weight newborns is significantly higher as compared to that of low birth weight newborns. Cord blood haemoglobin concentrations shows strong statistical significance with maternal anaemia. The birth order of the child has a prominent inverse effect on the cord blood haemoglobin values. Conclusions: There should nationwide improvement in the nutritional status of the girl child by dietary supplementations to improve the health of the generations to come. There should be proper birth spacing to prevent maternal and neonatal morbidities. Maternal anaemia needs early and aggressive treatment to minimize perinatal complications to both mother and the baby.